Tortilla Flat Illustration - Ruth Gannett:::Creator::::::::::::
Pen and ink drawing from Tortilla Flat, The Ruth Gannett illustrations are found in the Covici, Friede edition published in 1935 as well as the Collectors Reprints edition published in 1991. Pilon, Pablo, Jesus Maria, and Danny at the stove. (p.89)